Les logiques d’engagement dans la guerre d’indépendance au Venezuela. Une autre face de la guerre civile (1812-1818) - Véronique Hébrard (Amnis)
The aim of this article is to comprehend the forms and logic of civilian commitment in the war that shook Venezuela after 1812, through the examination of judicial archives. It also attempts to account for the actors’ systems of representation, at the individual and collective level, as well as discursive dynamics and acts, which fed the conflict and helped push it to extremes, notably by constructing an image of the enemy capable of warding off the civil character of the war. To do this, three aspects are given priority: the logic of commitment, the functioning of justice in time of war and its use by the actors.